Analysis of the Effect of Service Quality on Gojek Application User Satisfaction Using the Servqual Method - Iskantika, Yusliana; Nuryuliani, Nuryuliani (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to analyze the effect of service quality indicators (tangible, reliability, responsiveness, assurance, and empathy) on the satisfaction of Gojek application service users. The method used is quantitative with the population of all Gojek application users. The primary data source was obtained from an online questionnaire of 200 respondents in DKI Jakarta, using SEM (Structural Equation Modeling) and IBM AMOS software. The results showed that physical evidence indicators had a significant positive effect on Gojek application user satisfaction, while indicators of reliability, responsiveness, assurance, and empathy did not have a significant effect. The implication of this research is that physically visible aspects play an important role in influencing Gojek app user satisfaction, while other aspects may need to be reconsidered in service development strategies to improve overall user satisfaction. Quantitative analysis methods and SEM techniques also prove their importance in understanding the dynamics of the relationship between service quality and user satisfaction in the context of digital applications. The practical implication is that service providers can focus on improving physical evidence to improve user experience and maintain a strong customer base in the digital services industry.